The use of metformin for type 2 diabetes prevention: Observational multicenter study from Saudi Arabia - Alfayez, Osamah M.; Alsallum, Alanoud A.; Aljabri, Adnan F.; Almutairi, Faisal S.; Al-Azzeh, Ola; Almalki, Ohoud S.; Al Yami, Majed S.; Almohammed, Omar A. (Frontiers in Public Health, 2022)
Background: Patients with prediabetes are at higher risk of developing type 2 diabetes. While intensive lifestyle modification is the primary approach to delaying diabetes, metformin has been shown to be effective, especially among patients younger than 60 years and obese (body mass index (BMI) > 35 kg/m2), patients with fasting blood glucose ≥ 6.1 mmol/L or HbA1c ≥ 6%, and women with history of gestational diabetes. This study aimed to identify the prevalence of metformin use among prediabetes patients overall and patients who are more likely to benefit from metformin use per the ADA guidelines. Methods: A retrospective cohort study was conducted encompassing data from three tertiary care hospitals between January 2015 and June 2019. All patients aged 20 to 70 years with prediabetes (HbA1c of 5.7% - 6.4%) were included, while patients with an established diagnosis of diabetes, creatinine clearance less than 45 ml/min, using antihyperglycemic medications other than metformin, or on metformin for other indications were excluded. Prediabetes patients who are most likely to benefit from metformin for type 2 diabetes prevention are those younger than 60 years with a BMI ≥ 35 kg/m2, patients with fasting blood glucose ≥ 6.1 mmol/L or HbA1c ≥ 6%, and women with history of gestational diabetes. This study examined the prevalence of metformin use among all patients with prediabetes, as well as patients who would be more likely to benefit from metformin use per the ADA guidelines. Results: A total of 251 patients were included in this study; 52.2% were female, with a mean age of 47.0 (11.9) years and BMI of 32.3 (6.5) kg/m2, and the median HbA1c at baseline was 5.8% (5.7-6.0). Among the overall sample, 18 patients (7.2%) received metformin for the prevention of type 2 diabetes, 14 of those were from the groups that are more likely to benefit from metformin use per the ADA guidelines (9.9%). Conclusions: Among individuals with prediabetes in Saudi Arabia, metformin use was very low despite the evidence supporting its safety, convenience, and efficacy. Healthcare providers seemed hesitant to medicalize prediabetes.